The Australia-ASEAN Dialogue
XII, 270 p. 4 illus.
Keywords: This book examines the Australia-ASEAN Dialogue Partnership since its inception in 1974 and looks at the networks of engagement that have shaped relations across three areas: regionalism, non-traditional security, and economic engagement.